Effect of Colchicine on In Vitro Growth and Ploidicity of Crown Vetiver Plant (Vetiveria zizanioides L. Nash) - Sinta, Anisa Firmandanur; Widoretno, Wahyu (Graduate School, Universitas Brawijaya, 2020)
The goal of this research was to evaluate the effect of colchicine on the formation and growth of shoot from explant crowns by in vitro, as well as to obtain polyploidy vetiver plant (Vetiveriazizanioides L. Nash). Induction of polyploidy vetiver plants carried out by culturing explant crowns on MS media supplemented by 2 mg.L-1 BAP and colchicine (0, 30, 60, 90, 120 mg.L-1) for three weeks. Explant and formed shoot regenerated on MS media containing 1 mg.L-1 NAA. The generated plantlets acclimatized on the growing media (cocopeat: husk charcoal: compost = 1: 1: 2). Plant ploidy level of the plants regenerated from treated explant estimated by chromosome counting in root tips. The effect of colchicine on media was able to induce polyploidy in vetiver plants. Five mixoploids were obtained from explant treated colchicine. The vetiver mixoploid plants obtained were 20% and 62.5% from colchicine 60 mg.L-1 and 90 mg.L-1, respectively. The vetiver mixoploid plants consist of diploid (2n=2x=20) and triploid cells (2n=3x=30) or diploid (2n=2x=20) and tetraploid (2n=4x=40). The addition of colchicine in concentrations above 30 mg.L-1 caused inhibition of shoot formation and growth, even a concentration of 120 mg.L-1 caused explant death. However, 30 mg.L-1 colchicine could increase the number of formed shoots, while only 60 mg.L-1 and 90 mg.L-1 could be induced the mixoploidy in the vetiver plant. The results showed that colchicine treatment could increase ploidicity in vetiver plants in vitro, but caused inhibition of shoot formation and growth. Keywords : Chromosome, colchicine, in vitro, polyploid, Vetiveria zizanioides L. Nash.